Intermolecular enantioselective dearomatizing para-methoxylation of phenols using 2-iodoresorcinol/lactamide catalysts. (12th October 2022) - Kraszewski, Karol; Tomczyk, Ireneusz; Kalek, Marcin
Graphical abstract: Abstract: Intermolecular enantioselective oxidative para -dearomatization of phenols with the addition of methanol, catalyzed by a chiral 2-iodoresorcinol/lactamide, has been developed. The reaction allows for the synthesis of a broad range of 4-methoxy-2, 5-cyclohexadienone products with up to 62% ee (from 2, 4-disubstituted phenols in 43–62% ee; from a 3, 4-disubstituted phenol in 17% ee; from 4-substituted-1-napthols in 38–44% ee). Reported results constitute a proof of concept that the enantioselectivity in challenging intermolecular dearomatization of phenols can be considerably improved in a simple way, namely, by increasing the steric bulk of the coupling partner upon replacing water with methanol.